Taxonomic notes on Indolestes Fraser, 1922 (Lestidae, Zygoptera). 3. Male and clarified type locality of Indolestes anomalus Fraser, 1946 - Kosterin, Oleg E.; Garrison, Rosser; Kompier, Tom; Farrell, Dennis (Zootaxa, 2019)
The male of Indolestes anomalus Fraser, 1946 is described and the holotype female is depicted. Its occurrence in Vietnam, Thailand and Malaysia is discussed, and the type locality is clarified (South Vietnam, Đồng Nai River basin).